Analisis Postur Kerja Dengan Metode Nordic Body Map (NBM) Dan Rapid Office Strain Assessment (ROSA) Untuk Mengurangi Risiko Cedera Pada Departemen FAC Dan MIS Di PT. XYZ - Rhino Aryo Wicaksono; Kharisma Innayatul Zulfa; Adhi Wiratmoko (Universitas Pahlawan Tuanku Tambusai, 2024)
Employee well-being and health in the workplace is a top priority to maintain productivity and reduce the risk of injury. This study evaluates ergonomic risks in the Finance and Accounting (FAC) and Management Information Systems (MIS) departments at PT XYZ, a creamer industry company. Using the Nordic Body Map (NBM) and Rapid Office Strain Assessment (ROSA) methods, results showed a high level of ergonomic risk for 3 out of 4 employees, with one having a medium risk. Recommendations included work facility updates and employee awareness campaigns to improve ergonomic work practices. This research emphasizes the importance of office ergonomics in improving employee well-being and productivity, while reducing the risk of musculoskeletal injuries in modern work environments.